Cerebrospinal fluid lipocalin 2 in patients with clinically isolated syndromes and early multiple sclerosis. (October 2016) - Khalil, M; Renner, A; Langkammer, C; Enzinger, C; Ropele, S; Stojakovic, T; Scharnagl, H; Bachmaier, G; Pichler, A; Archelos, JJ; Fuchs, S; Seifert-Held, T; et al.
Background: Lipocalin 2 (LCN2) may be involved in the immunopathogenesis of multiple sclerosis (MS) and might further impact on iron homoeostasis. Brain iron accumulates in MS; however, the association to iron-related proteins is still unsolved. Objective: To investigate cerebrospinal fluid (CSF) and serum LCN2, transferrin (Trf) and ferritin in early MS in relation to disease evolution and longitudinal brain iron accumulation. Methods: We analysed CSF and serum LCN2 by enzyme-linked immunosorbent assay (ELISA) and Trf and ferritin by nephelometry in 55 patients (45 clinically isolated syndrome (CIS), 10 MS, median clinical follow-up 4.8 years) and 63 controls. In patients, we assessed sub-cortical grey matter iron by 3T magnetic resonance imaging (MRI) R2* relaxometry (median imaging follow-up 2.2 years). Results: Compared to controls serum ( p < 0.01), CSF ( p < 0.001) LCN2 and CSF Trf ( p < 0.001) levels were reduced in the patients. CSF LCN2 correlated with CSF Trf ( r = 0.5, p < 0.001). In clinically stable patients, CSF LCN2 levels correlated with basal ganglia iron accumulation ( r = 0.5, p < 0.05). In CIS, higher CSF LCN2 levels were associated with conversion to clinically definite MS ( p < 0.05). Conclusion: We demonstrate altered LCN2 regulation in early MS and provide first evidence for this to be possibly linked to both clinical MS activity and iron accumulation in the basal ganglia.